Stat1 is an inducible transcriptional repressor of neural stem cells self-renewal program during neuroinflammation - Imitola, Jaime; Hollingsworth, Ethan W.; Watanabe, Fumihiro; Olah, Marta; Elyaman, Wassim; Starossom, Sarah; Kivisäkk, Pia; Khoury, Samia J. (Frontiers in Cellular Neuroscience, 2023)
A central issue in regenerative medicine is understanding the mechanisms that regulate the selfrenewal of endogenous stem cells in response to injury and disease 1 . Interferons increase hematopoietic stem cells during infection by activating STAT1 2,3 , but the mechanisms by which STAT1 regulates intrinsic programs in neural stem cells (NSCs) during neuroinflammation is less known. Here we explored the role of STAT1 on NSC self-renewal. We show that overexpressing Stat1 in NSCs derived from the subventricular zone (SVZ) decreases NSC self-renewal capacity while Stat1 deletion increases NSC self-renewal, neurogenesis, and oligodendrogenesis in isolated NSCs.Importantly, we find upregulation of STAT1 in NSCs in a mouse model of multiple sclerosis (MS) and an increase in pathological T cells expressing IFN-g rather than interleukin 17 (IL-17) in the cerebrospinal fluid of affected mice. We find IFN-g is superior to IL-17 in reducing proliferation and precipitating an abnormal NSC phenotype featuring increased STAT1 phosphorylation and Stat1 and p16 ink4A gene expression. Notably, Stat1 -/-NSCs were resistant to the effect of IFN-g. Lastly, we identified a Stat1-dependent gene expression profile associated with an increase in the Sox9 transcription factor, a regulator of self-renewal. Stat1 binds and transcriptionally represses Sox9 in a transcriptional luciferase assay. We conclude that Stat1 serves as an inducible checkpoint for NSC self-renewal that is upregulated during chronic brain inflammation leading to decreased self-renewal.As such, Stat1 may be a potential target to modulate for next generation therapies to prevent progression and loss of repair function in NSCs/neural progenitors in MS.